2020
DOI: 10.1080/16506073.2020.1812709
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of relapse and recurrence following cognitive behavioural therapy for anxiety-related disorders: a systematic review

Abstract: Cognitive behavioural therapy (CBT) is an effective psychological treatment for anxiety-related disorders (anxiety disorders, post-traumatic stress disorder, and obsessivecompulsive disorder). However, relapse of anxiety symptoms is common following completion of treatment. This study aimed to identify predictors of relapse of anxiety after CBT for adult (18+) patients to enable the identification of 'at-risk' patients who could potentially benefit from relapse prevention interventions. A systematic review and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 38 publications
2
25
0
Order By: Relevance
“…Current research examining the maintenance of gains following therapy in neurotypical populations has recently been consolidated. Two systematic reviews have revealed that stressful life events predict an increased risk of relapse following cognitive behavioural therapy (CBT) for anxiety-related disorders (Lorimer et al, 2021) and depression (Wojnarowski et al, 2019). This is particularly pertinent as evidence preceding the pandemic indicated that anxiety disorders have recurrence rates of between 39% and 56% (Vervliet et al, 2013) and depression of between 50 and 80% (American Psychiatric Association, 2000).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Current research examining the maintenance of gains following therapy in neurotypical populations has recently been consolidated. Two systematic reviews have revealed that stressful life events predict an increased risk of relapse following cognitive behavioural therapy (CBT) for anxiety-related disorders (Lorimer et al, 2021) and depression (Wojnarowski et al, 2019). This is particularly pertinent as evidence preceding the pandemic indicated that anxiety disorders have recurrence rates of between 39% and 56% (Vervliet et al, 2013) and depression of between 50 and 80% (American Psychiatric Association, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…An increase in the rates of relapse following psychotherapy would worsen the already high global disease burden of common mental health conditions such as anxiety and depression (Lorimer et al, 2021). Additionally, for adults with IDs, access to psychological services has been impeded due to the pandemic (Purrington and Beail, 2021), therefore relapse not only causes emotional difficulties for individuals but also produces wider detrimental impacts such as inefficient service provision and increased health-care costs (Lorimer et al, 2021;Wojnarowski et al, 2019). Therefore, a service evaluation was conducted to explore the experiences of adults with ID living through the Covid-19 pandemic after completing a course of psychological therapy.…”
Section: Introductionmentioning
confidence: 99%
“…First, it is consonant with a growing re-emergence of interest in the establishment of a personalized psychiatry, and with similar reviews in other important areas of psychiatry 6,260 . Second, it resonates with systematic work on identification of treatment outcomes, and may help identify variables for potential inclusion in complex predictive models, including machine learning approaches 261,262 . Third, the literature suggests a number of clinically feasible measures, including self-report scales, that can potentially be included in future observational or intervention research.…”
Section: Discussionmentioning
confidence: 97%
“…While these findings need to be replicated in independent samples, our results are consistent with the observed difference in long-term outcomes across the two trials on this particular VR intervention ( 17 , 18 ), and suggest that it is indeed beneficial to explicitly promote transition to in-vivo exposure after completing VR exposure, and that this can be accomplished with brief oral and written instructions. Even in the broader field of cognitive behavioral therapy (CBT), where numerous studies have examined predictors of relapse ( 44 , 45 ), there has been very relatively little research on the associations between long-term symptom trajectories and post-treatment adherence to the therapeutic strategies taught and practiced during active treatment. This lack of comparable research also makes it difficult to interpret whether the self-rated compliance of 61% found in the current study is high or not.…”
Section: Discussionmentioning
confidence: 99%